Indian Economic Story Post 1990-91 And the Three Twins: A Comparative Analysis - NAKHATE, DR. VIDYA ARUN; KUMAR, DR. DHIRENDRA (The journal of contemporary issues in business and government, 2021)
The Post Independent India has largely experienced negative GDP growth in 1958, 1966, 1973, 1980’s, 2020-21. The post crisis years after 2008-09 though did not experience negative GDP growth but were very challenging. The years 1991, 2014-15 and 2020-21 have experienced twin deficit crisis, twin balance sheet syndrome and twin economic shocks (Demand & supply) respectively. The author has considered these years as three twins. The Researcher has tried to study the different macroeconomic variables to understand the nature and characteristics of these three twins, their commonality and differences. The researcher has considered Macroeconomic Stability Index to have a comparative analysis of three phases experiencing these three twins.